Evolutionary Game Analysis of the Social Co-governance of E-Commerce Intellectual Property Protection - Li, Ji; Xu, Chunming; Huang, Lufei (Frontiers in Psychology, 2022)
By introducing the theory of social co-governance into the field of e-commerce intellectual property protection, this paper builds an evolutionary game model among the government, e-commerce platforms, and rights holders, and studies the conditions under the stakeholders form a stable equilibrium state under different constraints. Combined with numerical simulation, the influence of individual factors and factor combinations on the system stability is analyzed. Results shows that: Strictly controlling the action costs and response costs of all parties can enhance their willingness to actively deal with infringement issues; reasonable adjustment of the reward and punishment measures of government supervisory agencies can produce sufficient reverse shock and positive guidance to platform and operators; penalties should be imposed on government supervisory agencies that are not sufficiently supervised; strengthen the construction of the social environment for intellectual property protection, improve the social benefits of actively responding to infringement issues, and increase the sense of acquisition by the government, platforms and rights holders. And it provides certain positive references and suggestions for the government to formulate relevant policies.